Pendidikan Nonformal dan Pembentukan Habitus Keislaman Anak Muslim: Refleksi Pengalaman Historis Bangsa Indonesia Era Pra-Kemerdekaan - Febriyantika Wulandari (Medan Resource Center, 2025)
Non-formal education holds a crucial position in the historical trajectory of Islamic education in Indonesia. During the pre-independence era, non-formal institutions such as pesantren, surau, langgar, meunasah, and traditional madrasahs served as primary social spaces where Muslim children received religious instruction and simultaneously strengthened their Islamic identity amid colonial pressures. This study aims to understand the role of non-formal education in shaping the Islamic habitus of Muslim children as part of the Indonesian nation’s historical experience prior to independence. Employing a qualitative approach through a literature-based method, this study utilizes various scholarly works, books, and journal articles relevant to the topic. Data were analyzed reflectively through secondary sources using the sociocultural framework and Pierre Bourdieu’s concept of habitus. The findings reveal that non-formal education during the pre-independence period functioned not only as a means of transmitting religious knowledge but also as a mechanism for reproducing social values, ethics, and solidarity within Muslim communities. Through participatory learning processes rooted in social experience, a strong Islamic habitus was cultivated among children characterized by religious discipline, respect for teachers, and a sense of communal belonging. These non-formal institutions also acted as arenas of cultural resistance against the secular and discriminatory nature of colonial education. This study concludes that the legacy of past non-formal education remains relevant for strengthening spiritual, moral, and social values within contemporary Islamic education.